Alumni events / Priestly Lanting Layang ... [et al.] - Layang, Priestly Lanting; Abang Shamsudin, Dayang Nurul Amieyda; Herman, Nurul Izzah; Standard, Stephanie Sonia; Mokhtar, Muhammad Adib Azfar (Perpustakaan Tun Abdul Razak, 2023)
Why alumni events? To gain a relationship with the past graduate, the university should keep attached to these alumni because they are still the ones who can make the university name brighter. Besides the staff and students, they are also the important people who can bring the university on the right path to maintain quality. The university can invite successful alums to make a speech to motivate the students.